Selective Multi Keys to Modify RSA Algorithm - Abdulrazzaq, Maiwan Bahjat (Sulaimani Journal for Pure and Applied Sciences, 2019)
The use of the internet and communication technology noticeably contributes to development in all branches of science. The data that is transferred to communication channel are unsecured. Cryptography including security and integrity is a domain that provides policies for having privacy of the data. Protection of the data transferred through the internet is very important since such data when transferred through an unprotected channel may be attacked by a third party. RSA represents one of the public key cryptography methods that generate the modulus using two primes. These two primes represent the weakness of RSA benefited from and used by attackers. This paper proposes a new modified RSA method using selective multi keys encryption and decryption for the same modulus instead of using two keys, one for encryption and the other for decryption. This new method guarantees and increases the security of RSA.
Keywords: Cryptography; public key cryptography; RSA algorithm; asymmetric key; symmetric key